Induction of remission in diabetes by lowering blood glucose - Weir, Gordon C.; Bonner-Weir, Susan (Frontiers in Endocrinology, 2023)
As diabetes continues to grow as major health problem, there has been great progress in understanding the important role of pancreatic beta cells in its pathogenesis. Diabetes develops when the normal interplay between insulin secretion and the insulin sensitivity of target tissues is disrupted. With type 2 diabetes (T2D), glucose levels start to rise when beta-cells are unable to meet the demands of insulin resistance. For type 1 diabetes (T1D) glucose levels rise as beta-cells are killed off by autoimmunity. In both cases the increased glucose levels have a toxic effect on beta-cells. This process, called glucose toxicity, has a major inhibitory effect on insulin secretion. This beta-cell dysfunction can be reversed by therapies that reduce glucose levels. Thus, it is becoming increasingly apparent that an opportunity exists to produce a complete or partial remission for T2D, both of which will provide health benefit.